Divide and Conquer - Organizing Component-based Adaptation - Scholz, Ulrich; Rouvoy, Romain (Electronic Communications of the EASST, 2008)
This paper introduces a divide and conquer approach for organizing the adaptation of distributed applications in a potentially large number of interacting middleware instances. In such an environment, a centralistic and static adaptation reasoning i) is inadequate and ii) gives the same priority to all applications. The divide and conquer method aims at minimizing the interference between running applications, allowing users to weight the priority of applications, and organizing the adaptation and the reasoning about the adaptation in a decentralized and flexible way.